Implementation of Carl Rogers' Humanistic Learning Theory in Islamic Religious Education Learning at MIS Miftahul Hasanah Binjai - Nasution, Nur Adilah; Najari, Muhammad (Lembaga Riset Mutiara Akbar, 2025)
The background of this research is to find solutions for how to develop Islamic religious education learning methods with techniques that pay attention to students' personal development and moral values. An alternative that can be done by teachers is to use humanistic learning theory. This research uses a descriptive method with a qualitative approach which will describe how the school implements this humanistic education. Data collection by conducting observations, interviews and documentation. The research results show that the learning process that applies humanistic education is going well, through learning designs such as: planning, implementation and evaluation. The supporting factors are teachers at MIS Miftahul Hasanah Binjai who follow current developments, a supportive school environment, adequate facilities and infrastructure. The inhibiting factors are the teacher's monotonous way of teaching, students who are difficult to manage, lack of mastery of the class by the teacher, due to the number of teachers being disproportionate to the number of students in the class.